The new frontiers of participatory evaluation: between challenges and opportunities - Lipari, Sabrina (Community Notebook. People, Education and Welfare in the Society 5.0, 2025)
This article explores the challenges and opportunities associated with evaluating self-entrepreneurship and youth empowerment projects, with a focus on an initiative carried out in the inland areas of Trentino and Basilicata. Through an analysis of the ecological value chain methodology developed by AICCON and applied to JA Italia ETS projects, we discuss how a well-structured evaluation can not only improve understanding of the impacts of such projects, but also address the difficulties in data collection and results measurement. Finally, the learning opportunities arising from evaluation are highlighted, emphasising the importance of adaptive approaches to ensure long-term success and sustainability.